Specyfika podkarpackiego okręgu nr 9 w wyborach do Parlamentu Europejskiego w 2014 roku - Maj, Przemysław (Polityka i Społeczeństwo, 2021)
The Subcarpathian Voivodeship is a specific region in terms of electoral prefer-ences. The results of the European elections in 2004, 2009 and 2014 indicated that results better than the national average were gained by right-wing parties (Liga Polskich Rodzin, Prawo i Sprawiedliwość) as well as “rural” committees (Polskie Stronnictwo Ludowe, Samoobrona). The aim of this article is to explain the factors influencing the electoral preferences.